Teaching strategies for neurodiversity and dyslexia in actor training sensing Shakespeare - Whitfield, Petronilla (Routledge, an imprint of the Taylor & Francis Group, 2020)
"Teaching Strategies for Neurodiversity and Dyslexia in Actor Training addresses some of the challenges met by acting students with dyslexia and highlights the abilities demonstrated by individuals with specific learning differences in actor training. The book offers six tested teaching strategies, created from practical and theoretical research investigations with dyslexic acting students, using the methodologies of case study and action research. Utilising Shakespeare's text as a laboratory of practice and drawing directly from the voices and practical work of the dyslexic students themselves, the book explores: - the stress caused by dyslexia and how the teacher might ameliorate it through changes in their practice - the theories and discourse surrounding the label of dyslexia - the visual, kinaesthetic and multisensory processing preferences demonstrated by some acting students assessed as dyslexic - acting approaches for engaging with Shakespeare's language, enabling those with dyslexia to develop their authentic voice and abilities - A grounding of the words and the meaning of the text through embodied cognition, spatial awareness and epistemic tools - Stanislavski's method of units and actions and how it can benefit and obstruct the student with dyslexia when working on Shakespeare - Interpretive Mnemonics as a memory support and hermeneutic process, and the use of colour and drawing towards an autonomy in live performance This book is a valuable resource for voice and actor training, professional performance, and for those who are curious about emancipatory methods that support difference through humanistic teaching philosophies"--Provided by publisher.